Green-Sustainable Recovery of Phenolic and Antioxidant Compounds from Industrial Chestnut Shells Using Ultrasound-Assisted Extraction: Optimization and Evaluation of Biological Activities In Vitro - Fátima Lameirão; Diana Pinto; Elsa F. Vieira; Andreia F. Peixoto; Cristina Freire; Stefania Sut; Stefano Dall’Acqua; Paulo Costa; Cristina Delerue-Matos; Francisca Rodrigues (Antioxidants, 2020)
Chestnut processing industry generates large amounts of by-products, including leaves, burs and shells that are a source of bioactive compounds. The purpose of this study was to establish an ultrasound-assisted extraction (UAE) of phenolic and antioxidant compounds from industrial chestnut shells. A central composite design (CCD) was conducted to analyze the effects of time (4−46 min) and temperature (34−76 °C) in the antioxidant activity (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP)) and total phenolic compounds (TPC) of chestnut shells extracts. The optimal extraction conditions were obtained at 70 °C for 40 min. The optimal extract was characterized regarding phenolic profile, radical scavenging capacity, and effects on intestinal and dermal cell lines. The optimal extract revealed high amounts of ellagic acid (40.4 µg/mg dw), followed by caffeic acid derivative (15.4 µg/mg dw) and epigallocatechin (15.3 µg/mg dw). Indeed, the extract exhibited the highest scavenging efficiencies against NO● (IC50 = 0.1 µg/mL) and HOCl (IC50 = 0.7 µg/mL) and did not conducted to a decrease on HaCaT and HFF-1 viability up to 100 μg/mL. Oppositely, a decrease on Caco-2 and HT29-MTX viability was observed. This study suggests that UAE could be a sustainable option to valorize chestnut shells as raw material for different industries.